MORPHOMETRIC CHARACTERISTICS OF TIBI BONE IN POSTNATAL ONTOGENESIS OF RABBITS OF DIFFERENT BREEDS - Yakubov Muzaffar Alimjonovich; Mirzoev Zoyir Rajabovich; Mukhtarov Elmurad Abdiglomovich (Journals Park Publishing, 2022)
The linear dimensions and absolute values of the weight of the leg bone in the postnatal ontogenesis of rabbits of the gray giant, white giant and flander breeds were studied. The specific dynamics of the growth of morphometric parameters of the tibia bone of rabbits in postnatal development was revealed. It was observed that the absolute values of the tibia bone mass, especially in rabbits of the 1st and 3rd groups after 21 days of postnatal ontogenesis, are greater than in the 2nd group.
Keywords: rabbit, gray giant, white giant and flander, leg bones, postnatal ontogenesis